The big city - Rickards, Lynne; Roberts, Ley Honor (Cambridge, U.K. : Cambridge University Press, 2017)
A boy and his father introduce the reader to a big city.
"UCL, Institute of Education."
1.2
K-3
K-3
Keywords: Cities and towns -- Juvenile fiction; Man-woman relationships -- Juvenile fiction; Cities and towns -- Fiction; Man-woman relationships -- Fiction; Cities and towns -- Fiction; Man-woman relationship -- Fiction; Readers (Publications)